O aborto na agenda pública brasileira e a influência do movimento de mulheres sobre o Estado: um estudo de debate contemporâneo - Pattaro Amaral, Fernanda [UNESP] (2009)
This research regards a study of the abortion in Brazil emphasizing the contemporary debate which we have two perspectives growing up: the abortion saw as a public health problem (by the rates of maternal mortality); and the abortion saw as a reproductive right. The perspective of the abortion as a reproductive right was successful in developed countries as the Unites States due to the feminist political mobilization which demanded the right of their own bodies. In the development countries as Brazil, this perspective was not the ideal ones to discuss this question. The brazilian feminism, at the first time, decided to denunciate the abortion clandestine and its consequences to the woman's health. Thus, some health professionals supported discussions about revisions on the legislation to reduce these incidences. Another aspect is about the social problem where women with more acquisitive power can make a safe abortion, and women with less acquisitive power have to do it in unsafe way. These denunciations got to the Legislative and a lot of projects were made about the abortion at all, authorizing or forbidding. But at this time just two of these projects were approved. This number is from the influence of the religious lobby on the Congress. The discussion of abortion is delicate because it means to reform some aspects of our historiccultural formation, involving woman at its representation in the society and the valorization of maternity in a religious atmosphere that disapprove abortion, and relation it with sin. These aspects help us to understand the difficulty of discussing it in the country. The actual debate about abortion in Brazil is about the medical abortion when the fetus has no brain. By the way, the health problem is the only way to discuss abortion today. So, the strategy of the feminism is still discusses abortion as a public health problem. This study pretends more than just to discuss and to understand...